1998
DOI: 10.1007/s100960050163
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Nosocomial Bloodstream Infections in Belgium, 1992-1996

Abstract: The main results of the bloodstream infection (BSI) component of the Belgian National Programme for the Surveillance of Hospital Infections (NSIH project) are reported. From October 1992 to September 1996, 117 hospitals (59.1% of Belgian acute-care institutions) reported 13678 nosocomial BSIs. The incidence was 7.05 BSI episodes per 10000 patient-days. The incidence of BSI increased with hospital size and over time. Bloodstream infections were secondary to an infectious body site in 40.3% of the episodes, cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
1
3

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 21 publications
2
22
1
3
Order By: Relevance
“…and Gram-negative bacilli have been reported as the most common aetiological agents of CR-BSI, which is consistent with data from our institution [6]. We found that 2·3% of all our CR-BSI episodes were due to less common microorganisms and this accords with other surveillance studies in the literature which report an incidence of <5% for such organisms from CR-BSI [7,8].…”
supporting
confidence: 95%
“…and Gram-negative bacilli have been reported as the most common aetiological agents of CR-BSI, which is consistent with data from our institution [6]. We found that 2·3% of all our CR-BSI episodes were due to less common microorganisms and this accords with other surveillance studies in the literature which report an incidence of <5% for such organisms from CR-BSI [7,8].…”
supporting
confidence: 95%
“…Invasive candidiasis has emerged as an important nosocomial infection, especially among critically ill patients [1][2][3][4][5]. From the 1980s to the end of the 1990s, an increasing trend of candidaemia prevalence became apparent, which was followed by a period of relative stability [6][7][8][9].…”
Section: Epidemiology and Resistance Profilesmentioning
confidence: 99%
“…La infección del torrente sanguíneo es la tercera causa de infección nosocomial a nivel internacional y representa el 19% de este tipo de infecciones (2,3,4).…”
Section: Discussionunclassified
“…En las últimas décadas, el uso de catéteres intravasculares (CIV) (1) se ha incrementado en las unidades de cuidados intensivos (UCI) (2,3); así como en los servicios de hospitalización (23,7%) y como consecuencia han aumentado las complicaciones asociadas a su uso: sepsis, infecciones del torrente sanguíneo (ITS) y colonización de catéter (3,4).…”
Section: Introductionunclassified